An investigation into problems facing small-to-medium sized enterprises in achieving growth in the Eastern Cape : enhancing the strategy for developing small 'growth potential' firms in the Eastern Cape - Sha, Shafeek (Rhodes University, Faculty of Commerce, Department of Management, 2006)
As the world economy continues to move towards increased integration, some of the greatest opportunities for Small-to-Medium Sized Enterprises (SMEs) will derive from their ability to participate in the global marketplace. It is generally accepted that SMEs are becoming increasingly important in terms of employment, wealth creation, and the development of innovation. However, there are considerable doubts about the quality of management in this sector with policy-makers suggesting that there are particular weaknesses in innovation, a lack of financial acumen, marketing, entrepreneurial flair, practical knowledge, and human resource management. As a result, many firms do not reach their full potential and fail to grow. According to organisational life cycle models, the introductory phase is particularly important since it is generally known and accepted that there is a high mortality rate of SMEs within the first two years. Given this high failure rate, it becomes vital to research the factors/characteristics/management abilities that are required to enable the SME to survive and indeed progress to the growth phase of the organizational life cycle. This research seeks to investigate the internal and external factors that are consistent in the success of SMEs who have reached the growth phase. A significant contribution to the enhancement of the growth potential of a firm will be made through the understanding of these factors.
Keywords: Small business -- Management; Small business -- South Africa -- Eastern Cape; Small business -- South Africa -- Eastern Cape -- Growth; Business enterprises -- Economic aspects -- South Africa -- Eastern Cape; Economic development -- South Africa -- Eastern Cape